2003
DOI: 10.1021/ja0374877
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of CaCO3 Crystals of Complex Morphology Using a Fungus and an Actinomycete

Abstract: The biosynthesis of CaCO3 by reaction of aqueous Ca2+ ions with a fungus, Fusarium sp., and an actinomycete, Rhodococcus sp. (both plant organisms), is described. In the case of the fungus, cruciform-shaped calcite crystals are obtained (SEM picture A) while the actinomycete yielded the unstable polymorph of CaCO3, vaterite (SEM picture B). Specific proteins secreted by the microorganisms are responsible for the morphology and crystallography control observed. A highlight of this approach is that the microorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 17 publications
0
60
0
1
Order By: Relevance
“…Rautaray et al [97,98], Ahmad et al [99] and Sanyal et al [100] performed similar studies in which they demonstrated that fungal biomass exposed to significant concentration of Ca 2+ (as CaCl2) leads to CaCO3 biomineralization. They observed very distinct morphologies of crystals depending on the fungal species involved and proposed that specific proteins were responsible for this.…”
Section: Fungal Caco3 Produced In the Laboratorymentioning
confidence: 90%
“…Rautaray et al [97,98], Ahmad et al [99] and Sanyal et al [100] performed similar studies in which they demonstrated that fungal biomass exposed to significant concentration of Ca 2+ (as CaCl2) leads to CaCO3 biomineralization. They observed very distinct morphologies of crystals depending on the fungal species involved and proposed that specific proteins were responsible for this.…”
Section: Fungal Caco3 Produced In the Laboratorymentioning
confidence: 90%
“…The presence of proteins was indicated by the amide I signature at 1655 cm À1 (Rautaray et al, 2003). Amino acids in Bacto Casitone account for the amide shoulder in the abiotic precipitates.…”
Section: Biotic and Abiotic Vaterite Precipitationmentioning
confidence: 99%
“…Up to now, the size, morphology, crystallization and growth of calcium carbonate have been widely studied in the presence of organic templates, biomacromoleculars, or polymers [21][22][23][24] with regular surface-relief structures had been synthesized by templating methods in the presence of PAA, which have never been seen in natural biominerals [25]. In addition, cruciform-shaped calcite particles have been obtained using microorganisms [26]. Furthermore, porous single-crystalline CaCO 3 had been made from a simple hydrothermal treatment [27].…”
Section: Introductionmentioning
confidence: 99%